Acute onset of tetraparesis, arreflexia and respiratory distress in an otherwise healthy male. (21st December 2010) - Hamele, Mitchell; Mount, Cristin A
Abstract : The patient is a previously healthy Eastern-African man in his late 20s, with unknown vaccination status who presented to a US Army Combat Hospital in Iraq with acute upper and lower extremity weakness progressing to respiratory distress requiring intubation over the course of 12 h. His only antecedent symptoms were weakness and nausea. Laboratories including complete blood count, C reactive protein, cerebrospinal fluid analysis, venous blood gas, rapid HIV and chemistry were normal. Non-contrast head CT was normal. The patient was extubated after 24 h but continued to exhibit 2/5 strength in bilateral upper and lower extremities with absence of deep-tendon reflexes. At 48 h of illness it was discovered that the prior to his presentation the patient had a significant life stressor which had since been resolved. Upon discovery that this stressor had been resolved, the patient's symptoms improved over the subsequent 4–6 h and was discharged after 24 h without further complication.